Potential ancillary services of electric vehicles (vehicle-to-grid) in Indonesia. (October 2018) - Huda, Muhammad; Aziz, Muhammad; Tokimatsu, Koji
Abstract: Many countries committed to promoting eco-friendly transportation by accelerating the adoption of electric vehicles (EVs) in their country due to their beneficial feature, including in Indonesia. The ancillary services by EVs will be one of solution for power system due to their unique characteristic as energy storage. Indonesia is one of the developing countries that has a thousand islands which are mostly not connected to each other. Java-Madura-Bali (JAMALI) system is one of the large systems that has energy mix which is mainly produced by coal-fired power plant and limited energy storage. Large capacity battery from penetrated EVs in the future might be a good opportunity to support the grid, with time mapping for charging and discharging. Duration and period of opportunity can be determined by frequency recognition that has been measured for 1 month. This paper shows the opportunity of parked EVs utilization by releasing and absorbing the electricity for the load leveling and frequency regulation. The impacts of EVs adoption and V2G participation rates, which are motivated by some incentive from Transmission Service Operator (TSO), are analyzed. The results show that controllable charging and discharging behaviors of EVs have led to the idea of EVs utilization for supporting the grid. The feasibility of vehicle-to-grid (V2G) in Indonesian electrical grid is evaluated in this study. The evaluated ancillary services include load leveling and frequency regulation.